INTENSI PENGELOLAAN BISNIS BERBASIS DIGITALISASI CASH FLOW: BERSAMA MITRA UMKM KLASTER BANDENG KOTA SEMARANG - Aprih Santoso; Saifudin Saifudin; Ardiani Ika Sulistyawati (Jurnal Abdimas Bina Bangsa, 2024)
This Community Service Partner, namely the Semarang Bandeng Cluster MSME actors, faces the problem of not being able to manage their MSME finances properly, especially in managing receipts and expenses and separating personal finances from finances for business. On the one hand, reduced revenues due to the global food crisis have an impact on irregular income for MSMEs. On the other hand, increased expenditure, due to the needs and prices of consumer goods also makes it difficult to manage MSME finances. This is the background of the Community Service Team to be interested in doing community service for members of the Semarang Bandeng Cluster MSME Actors. PkM Method with introductory training on Business Management based on Cash Flow Digitalization. The results of PkM, MSME actors in the Semarang Bandeng cluster. understand and be able to carry out MSME financial management integrated with Cash Flow Digitalization neatly and well